Overcoming the Blood-Brain Barrier for Chemotherapy: Limitations, Challenges and Rising Problems - Wang, Zhaoye; Sun, Hui; Sebastian Yakisich, Juan (Anti-Cancer Agents in Medicinal Chemistry, 2014)
Treatment of brain tumors with chemotherapy is limited mostly because of delivery impediments related to the blood-brain barrier (BBB). For gliomas, the most common and aggressive primary brain tumor, treatment includes surgery, radiotherapy, and chemotherapy usually administered orally or intravenously. These routes do not deliver effective concentrations. To complicate matters, chemotherapy is usually a long treatment. Therefore, transient disruption of the BBB is likely insufficient to deliver effective intratumoral concentrations of anticancer drugs. This review briefly updates current strategies for overcoming the BBB with emphasis on their limitations and challenges intrinsic to the biology of cancer cells.
Keywords: blood brain barrier